A Discursive Reassessment of the World Information and Communication Order: Social Media Bridged the Gap - Inobemhe, Kelvin; Ja'afaru, Sharifatu; Santas, Tsegyu; Obiechina, Chika; Okpodu, Olushola (The Journal of Society and Media, 2025)
The World Information Order otherwise known as the New World Information Order (NWIO) can also be referred to or viewed as the New World Information and Communication Order (NWICO). The term or concept describes the aspirations and yearnings of the Global South for the establishing of a world where there is democratisation of the international communication system and a rebalancing of the global information flow channels. This conceptual study sought to reassess the concept in light of the development and advancement in technologies including social media – where information flow has been liberalised in diverse ways. The discourse is built around and/or aligned to a democratic liberal approach in respect of the use of social media in the digitally evolving world. The researchers argued that social media reinvigorated the quest by the Global South to ensure information flow worldwide and that is an indication of a fight for democratisation of the communication system. The study concluded that though the traditional media circle gradually tilts to all-encompassing communication and information in the world, the pace is slow and that gap created is now (in some dimension) bridged by social media platforms – Facebook, Instagram, Twitter (now X) and many more.